PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN KODULAR PADA MATA PELAJARAN BIOLOGI KELAS VII SMP NEGERI 5 TAEBENU SATAP - Taku Neno, Khatrin Juliani; Benufinit, Yonly; Amheka, Aranci (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2024)
This study aims to describe the feasibility and effectiveness of android-based biology learning media using kodular in class VII of SMP Negeri 5 Taebenu Satap. This type of research is quantitative with the method used is research and development (R&D). The population of class VII students of SMP Negeri 5 Taebenu Satap is 34 people. The sample is 17 people. The instruments used in this study are instruments in the form of observation, interviews, questionnaires, tests and documentation studies. The development model of this learning media was developed based on the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The data analysis method used is the one group pretest-posttest design experimental method. The output of this android-based learning media is in the form of an Application (Apk) that can be accessed using android, making it easier for students in the learning process. Based on the results of the trials conducted, the validation data obtained by material experts with an average of 98.3% is in the very good category, so that the material in the media is said to be very valid, while the validation results of media expert 1 media expert 2 with an average of 92.5% are in the very good category, and student responses to learning media with an average of 86.3% are in the Very Good category, so that android-based learning media is said to be very valid. Based on the results of the pretest and posttest calculated using the N-Gain Score with an average of 0.7889 is in the high category, and the N-Gain Percent value with an average of 78.89% is in the effective category. It can be concluded that android-based biology learning media in the biology subject of class VII of SMP Negeri 5 Taebenu Satap is feasible and effective.